Virtual Violence and New Media Ethics: The Boundary between Legitimate and Harmful Expressions - Sazali, Hasan; Matondang, Abdul Rahman; Mukhtar, Desvi Yanti; Rasyidah, Rasyidah (Universitas Gadjah Mada, 2024)
This research delves into the complexity of virtual violence in the realm of New Media ethics, focusing on the blurred boundary between legitimate expression and harmful threats. Within the context of the rapid growth of digital platforms, issues pertaining to ethics in online discourse and behavior are gaining increasing attention. The objective of this study is to explore the dynamics of the transition between creative expression and aggressive online behavior, as well as to identify its implications for individuals and society. The research employs a descriptive-analytical approach through a literature review. The literature review is conducted to delve into the concept of virtual violence, New Media ethics, and debates surrounding the demarcation between expression and threats. The findings of the research reveal the complexity in distinguishing between expression and threats within the context of virtual violence. Factors such as intent, context, and the impact of digital content play a significant role in determining ethical boundaries. While certain content evidently constitutes genuine threats, many cases require careful analysis to differentiate legitimate expression from unethical aggressive behavior. This research provides a deeper understanding of the dynamics of virtual violence within the realm of New Media ethics. Emerging implications and recommendations include the role of online platforms in developing clearer guidelines and the necessity for enhanced digital literacy to aid individuals in comprehending the social and moral impacts of their online behavior. This study contributes to the ongoing discourse concerning ethics in the digital world.